Changes in health behaviors and conditions during COVID-19 pandemic strict campus lockdown among Chinese university students - Zhang, Boyi; Lei, Si Man; Le, Shenglong; Gong, Qiang; Cheng, Sulin; Wang, Xiuqiang (Frontiers in Psychology, 2022)
Objective To explore how a stringent campus lockdown affects the physical activity (PA), sleep and mental health of Chinese university students living in student dormitories during the COVID-19 pandemic. Methods Data on PA, sleep and mental health were collected between 24 March and 4 April 2022 from 2084 university students (mean age = 22.4 years, 61.1% male students) via an online questionnaire distributed by the students’ advisers of each dormitory. The Chinese short version of the International Physical Activity Questionnaire (IPAQ-C), Athens Insomnia Scale (CAIS) and General Health Questionnaire 12-item (GHQ-12) were applied. The Mann–Whitney test and Kruskal-Wallis tests were used to evaluate the PA profile differences between genders, before and during the lockdown period and between students’ living environments. Chi-squared (χ2) or Fisher’s exact test was used to assess changes in health behaviors by gender and students’ living environment compared to before the lockdown. A mediation model was used to examine whether sleep disorder mediated the relationship between PA and mental health in different students’ living environments. Results Participants reported a significant decrease in weekly total PA levels (63.9%). Mean daily sedentary time increased by 21.4% and daily lying time increased by 10.7% compared to before lockdown. Among the participants, 21.2% had experienced insomnia, and 39.0% reported having high mental distress. Female students reported 10% higher rates of sleep disorders than male students (p < 0.001), and also experienced a higher incidence of mental disorders (p < 0.001). Students living with three roommates had a larger decrease in frequencies and durations of participation in light PA than other students (p < 0.001). PA was negatively associated with sleep and mental health, and sleep disorder was a mediating factor between PA and mental health in the students living with two and three roommates. Conclusion This study showed that strict lockdowns within university dormitories during the COVID-19 pandemic had a negative effect on the health of university students by changing their health behaviors, physical activity and sleep. Our findings indicate a need for strategies to promote an active lifestyle for students in space-limited dormitories in order to maintain health during a prolonged lockdown.